2021
DOI: 10.1038/s41419-021-04460-7
|View full text |Cite
|
Sign up to set email alerts
|

USP3 promotes gastric cancer progression and metastasis by deubiquitination-dependent COL9A3/COL6A5 stabilisation

Abstract: As an important regulator of intracellular protein degradation, the mechanism of the deubiquitinating enzyme family in tumour metastasis has received increasing attention. Our previous study revealed that USP3 promotes tumour progression and is highly expressed in gastric cancer (GC). Herein, we report two critical targets, COL9A3 and COL6A5, downstream of USP3, via the isobaric tags for relative and absolute quantification technique. Mechanistically, we observed that USP3 interacted with and stabilised COL9A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…The latter operates by facilitating cancer cell growth and invasion by controlling E-cadherin-Src signalling and cell–cell adhesion. The same goes for COL9A3 [ 47 ], which is involved in matrix synthesis and controls its degradation. It was also identified as significantly associated with the prognosis of TNBC in an independent prognostic signature [ 48 ].…”
Section: Discussionmentioning
confidence: 93%
“…The latter operates by facilitating cancer cell growth and invasion by controlling E-cadherin-Src signalling and cell–cell adhesion. The same goes for COL9A3 [ 47 ], which is involved in matrix synthesis and controls its degradation. It was also identified as significantly associated with the prognosis of TNBC in an independent prognostic signature [ 48 ].…”
Section: Discussionmentioning
confidence: 93%
“…Because HIV-1 Vif antagonizes A3G antiviral function by forming viral-specific cullin 5-RING ligase (CRL5) E3 ubiquitin ligase to promote the polyubiquitination and degradation of A3G, [ 5 , 52 , 53 ] we next determined whether the loss or gain of USP3 affected A3G expression in the presence of Vif. We found that increasing the level of USP3 expression effectively inhibited HIV-1 Vif-induced A3G degradation [Figure 1 G], while silencing endogenous USP3 enhanced it [Figure 1 H].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that USP3 plays a crucial role in numerous biological processes by deubiquitinating some host factors [54,66–70] . For example, USP3 regulates cancer progression and metastasis by deubiquitinating the Kruppel-like factor 5 (KLF5), stabilizing p53 or deubiquitination-dependent COL9A3/COL6A5 [53,71,72] . USP3 has also been identified as a novel regulator of histone H2A and H2B ubiquitination, highlighting its role in preventing replication stress and suggesting its involvement in the response to DNA double-strand breaks [55,70] .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al identified differentially expressed proteins in BGC-823 cells stably expressing USP3 [ 21 ]. Among them, SUZ12, a scaffolding component of the PRC2 complex, and COL9A3/COL6A5, collagen family members, were deubiquitinated and stabilized by USP3, which accounts for its role in promoting invasion and migration [ 21 , 22 ]. In addition to SUZ12, the core PRC2 complex also comprises the histone methyltransferase EZH2 and the scaffolding component EED.…”
Section: Usps and Gcmentioning
confidence: 99%